Comparison of the Retinal Straylight in Pseudophakic Eyes with PMMA, Hydrophobic Acrylic, and Hydrophilic Acrylic Spherical Intraocular Lens - Ya-wen Guo; Jun Li; Hui Song; Xin Tang (Journal of Ophthalmology)
Purpose. To investigate the intraocular straylight value after cataract surgery. Methods. In this study, 76 eyes from 62 patients were subdivided into three groups. A hydrophobic acrylic, a hydrophilic acrylic, and a PMMA IOL were respectively, implanted in 24 eyes, 28 eyes, and 24 eyes. Straylight was measured using C-Quant at 1 week and 1 month postoperatively in natural and dilated pupils. Results. The hydrophilic acrylic IOLs showed significantly lower straylight values than those of the hydrophobic acrylic IOLs in dilated pupils at 1 week and 1 month after surgery (P<0.05). However, the straylight values of the hydrophilic acrylic IOLs were the lowest among the three IOL groups. No significant difference was observed in straylight between 1 week and 1 month postoperatively in each group with natural and dilated pupils (P>0.05). Moreover, no significant difference was found in straylight between natural and dilated pupils in each group at 1 week and 1 month postoperatively (P>0.05). Conclusions. Although the hydrophobic acrylic IOL induced more intraocular straylight, straylight differences among the 3 IOLs were minimal. Pupil size showed no effect on intraocular straylight; the intraocular straylight was stable 1 week after surgery.